High dose rate and flattening filter free irradiation can be safely implemented in clinical practice. (3rd October 2015) - Dubois, Ludwig; Biemans, Rianne; Reniers, Brigitte; Bosmans, Geert; Trani, Daniela; Podesta, Mark; Kollaard, Robert; Rouschop, Kasper ma; Theys, Jan; Vooijs, Marc; Pruschy, Martin; Verhaegen, Frank; et al.
Abstract : Purpose : We hypothesize that flattening filter free (FFF) high dose rate irradiation will decrease cell survival in normal and cancer cells with more pronounced effects in DNA repair deficient cells. Additionally, we hypothesize that removal of the flattening filter will result in an enhanced relative biological effectiveness independent of the dose rate. Materials and methods : Clonogenic survival was assessed after exposure to dose rates of 4 or 24 Gy/min (FFF 10 megavolt [MV] photon beam) using a Varian TrueBeam accelerator. Additionally, cells were exposed to 4 Gy/min with or without flattening filter. Relative biological effectiveness estimations were performed comparing the different beam photon spectra. Results : Cell survival in tumor and normal cell lines was not influenced by high dose rate irradiation. The intrinsic radiation sensitivity of DNA repair deficient cells was not affected by high dose rate compared to normal dose rate. Furthermore, the relative biological effectiveness was not significantly different from unity in any of the cell lines for both FFF and conventional flattened beam exposures. Conclusions : High dose rate irradiation did not affect long-term survival and DNA repair for cell lines of different tissues. This suggests that high dose rate does not influence treatment outcome or treatment toxicity and could be safely implemented in clinical routine.